Merjenje medvrstniškega nasilja: opis metodologije kvantitativne raziskave - Košir , Katja; Špes, Tanja (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
In the past, the measurement of peer violence was carried out mainly using quantitative methods, mostly with self-assessment questionnaires, but in recent years the phenomenon has also been studied using qualitative methods and the mixed-approach method. In the introduction, the paper briefly outlines the measurement of peer violence, and then focuses on the description of the methodology of the quantitative research that we conducted within the project Social context as a factor of peer violence: how to contribute to an inclusive school by creating a positive peer culture?. The key purpose of the quantitative research was to examine the mutual relationship between indicators of social dynamics in the classroom and students' involvement in peer violence throughout the school year, and then, based on the data, to develop guidelines for students and school employees to prevent and respond to peer violence. Students in the 8th and 9th grades participated in a longitudinal study with three measurements, which was conducted in 118 primary schools in Slovenia in the 2022/2023 school year.